Gut microbiome and metabolic profiles of mouse model for MeCP2 duplication syndrome - Junfang Wu; Qingyu Hu; Xiaoping Rao; Hongyang Zhao; Huiru Tang; Yulan Wang (Brain Research Bulletin, 2024)
The extra copy of the methyl-CpG-binding protein 2 (MeCp2) gene causes MeCP2 duplication syndrome (MDS), a neurodevelopmental disorder characterized by intellectual disability and autistic phenotypes. However, the disturbed microbiome and metabolic profiling underlying the autistic-like behavioral deficits of MDS are rarely investigated. Here we aimed to understand the contributions of microbiome disruption and associated metabolic alterations, especially the disturbed neurotransmitters in MDS employing a transgenic mouse model with MeCP2 overexpression. We analyzed metabolic profiles of plasma, urine, and cecum content and microbiome profiles by both 16 s RNA and shotgun metagenomics sequence technology. We found the decreased levels of Firmicutes and increased levels of Bacteroides in the single MeCP2 gene mutation autism-like mouse model, demonstrating the importance of the host genome in a selection of microbiome, leading to the heterogeneity characteristics of microbiome in MDS. Furthermore, the changed levels of several neurotransmitters (such as dopamine, taurine, and glutamate) implied the excitatory-inhibitory imbalance caused by the single gene mutation. Concurrently, a range of microbial metabolisms of aromatic amino acids (such as tryptophan and phenylalanine) were identified in different biological matrices obtained from MeCP2 transgenic mice. Our investigation revealed the importance of genetic variation in accounting for the differences in microbiomes and confirmed the bidirectional regulatory axis of microbiota-gut-brain in studying the role of microbiome on MDS, which could be useful in deeply understanding the microbiome-based treatment in this autistic-like disease.